A CHARACTERIZATION OF EXTREMELY AMENABLE SEMIGROUPS (Journal of Sciences, Islamic Republic of Iran)
Let S be a discrete semigroup, m (S) the space of all bounded real functions on S with the usualsupremum norm. Let Acm (S) be a uniformly closed left invariant subalgebra of m (S) with 1 c A. We say that A is extremely left amenable if there isamultiplicative left invariant meanon A. Let P = {h ?A: h =|g-1,g | forsome g ?A, s ?S}. It isshown that . A is extremely left amenable if and only if there is a mean ? on A such that ?(PA) = 0.